2002
DOI: 10.1902/annals.2002.7.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Genes of Periodontopathogens Expressed During Human Disease

Abstract: MAT has proven useful in identifying previously unknown in vivo-induced genes that are likely involved in virulence and are thus excellent candidates for use in diagnostic : and therapeutic strategies, including vaccine design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Studies using in vivo induced antigen technology (IVIAT) [22] have the potential to identify large numbers of immunogenic antigens. The technique has been used to screen the entire A. actinomycetemcomitans genome and revealed 116 in vivo expressed antigens [23]. Further investigations using this method have shown that patients have a significantly greater serum antibody titer against six antigens than healthy controls, which supports the in vivo expression of these antigens, and even suggests their usefulness as disease markers [24].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies using in vivo induced antigen technology (IVIAT) [22] have the potential to identify large numbers of immunogenic antigens. The technique has been used to screen the entire A. actinomycetemcomitans genome and revealed 116 in vivo expressed antigens [23]. Further investigations using this method have shown that patients have a significantly greater serum antibody titer against six antigens than healthy controls, which supports the in vivo expression of these antigens, and even suggests their usefulness as disease markers [24].…”
Section: Introductionmentioning
confidence: 91%
“…Periodontal health was defined as no periodontal pockets exceeding 4 mm in a full dentition (28 teeth) and no attachment loss of more than 1 mm at more than one site, whereas gingival bleeding after probing indicative of gingival inflammation could occur. The mean age of the Moroccan AgP subjects was 18.5 years (range [14][15][16][17][18][19][20][21][22][23] and of the healthy control subjects 21.8 years (range 15-28). The mean age of the Danish AgP subjects was 36.8 (range 28-47) and of the healthy control subjects 30 years (27 and 33).…”
Section: Patient and Control Seramentioning
confidence: 99%
“…Moreover, many oral organisms including A. actinomycetemcomitans, P. gingivalis, F. nucleatum and S. gordonii have been shown to modulate expression of individual genes in epithelial cells (Belton et al 1999;Cao et al 2004;Darveau et al 1998;Fives-Taylor et al 1999;Guthmiller Lally and Korostoff 2001;Haraszthy et al 2000;Holt et al 1999;Korostoff et al 1998;Korostoff et al 2000;Lamont et al 1995;Lamont and Jenkinson 1998;Meyer Sreenivasan and Fives-Taylor 1991;Meyer Lippmann and Fives-Taylor 1996;Meyer Mintz and Fives-Taylor 1997;Nakhjiri et al 2001;Noguchi et al 2003;Shenker et al 1999;Shenker et al 2000;Shenker et al 2001;Song et al 2002;Yilmaz Watanabe and Lamont 2002;Yilmaz et al 2003;Zhang et al 2001a;Zhang Pelech and Uitto 2004;. Thus epithelial cells are capable of sensing and responding to oral bacteria at the transcriptional level.…”
Section: The Subgingival Microbial Challengementioning
confidence: 99%
“…Therefore, it is of importance to understand the mechanisms controlling the expression of these genes. In the case of Aa, Song et al [40] Cao et al [41], and Handfield et al [42] used an In Vivo Expression Technology (INVET) system to demonstrate the expression of 116 genes whose expression was induced following Aa infection of periodontitis patients, that were not expressed during in vitro growth of Aa on culture media. Some of these observations may well be explained by the findings of the present investigation.…”
Section: Resultsmentioning
confidence: 99%